Are acute and chronic saltwater fish studies required for plant protection and biocidal product active substance risk assessment?. (21st January 2014) - Wheeler, James R.; Maynard, Samuel K.; Crane, Mark
Abstract The acute and chronic toxicity of chemicals to fish is routinely assessed using fish acute and early life stage (ELS) test results, usually with freshwater species. Under some regulations with certain substances, however, data on saltwater species may also be required. Evidence from earlier studies suggests that saltwater fish species are generally no more sensitive than freshwater species and that when they are more sensitive to a substance the difference in sensitivity is usually less than a factor of 10. However, most of these studies concentrated on acute lethal toxicity results for a wide range of substances and across a range of taxonomic groups. In the present study, the authors compare freshwater and saltwater acute median lethal concentration (LC50) and chronic ELS no‐observed‐effect concentration (NOEC) results from standardized regulatory studies specifically for fish species exposed to the same plant protection or biocidal product active substances to determine the value of testing in both freshwater and saltwater fish. The results suggest that, in most cases, use of a freshwater fish 96‐h LC50 or longer‐term ELS NOEC should be sufficient to protect saltwater species. In a small number of cases (12%), saltwater ELS NOECs were more sensitive by a factor >10, although differences in sensitivity were not consistent for this small number of substances when 96‐h LC50 and longer‐term ELS NOECs were compared. It is debatable whether such a low probability merits the additional animal use required to run saltwater fish tests, especially when onshore contaminants released to estuaries and coastal environments are likely to be diluted many‐fold when compared with concentrations found in freshwaters. Environ Toxicol Chem 2014;33:703–707. © 2013 SETAC